(3GdBOGH GdeMbbI aj eYJHQGJ GdHfObIs - (3GdMSjf Hf eMeO Hf GdMSjf GdGHQjbj GdMHGfj GdMVQejs ((3eMeO Hf SYjO GdSdai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY cd TF Ndbg hHYO , aEfi deG CdaJ GdQSGdI GdehSheI HJMQjV GdENhGf GdcQGe hHPd GdfUjMI ai GdJMQR ef jGe GddFGe hCaYGdge GdbHjMIhYfO JeGe gPg GdQSGdI SeGgG HYV GdaVdGA HGdBOGH s
(3BNQgG (B:s
(3hdjS dgeG hdG dZjQgG eOM Ch Pe CMOgeG eWdbkG GfJgi hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs